2014
DOI: 10.3325/cmj.2014.55.468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of mono-compound topical treatments for reduction of intraocular pressure in patients with primary open angle glaucoma or ocular hypertension: an overview of reviews

Abstract: AimTo evaluate the existing evidence on relative efficacy and tolerability of topical mono-compound intraocular pressure (IOP)-lowering drugs in treatment of primary open angle glaucoma (POAG) and ocular hypertension (OHT).MethodsIn this systematic review of systematic reviews/meta-analyses of randomized controlled trials a thorough and sensitive search of PubMed, Embase and Cochrane Databases was performed. Individual study methodological quality and quality of evidence were assessed using the AMSTAR checklis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
7
0
3
Order By: Relevance
“…Это наиболее физиологический путь оттока камерной влаги, поскольку в нем не участвует уменьшение выработки камерной влаги. Эффективность и физиологичность гипотензивного действия -это первая причина для выбора синтетических простагландинов в качестве препаратов первого выбора в лечении глаукомы [6,7,19,21].…”
Section: клінічна офтальмологія введениеunclassified
“…Это наиболее физиологический путь оттока камерной влаги, поскольку в нем не участвует уменьшение выработки камерной влаги. Эффективность и физиологичность гипотензивного действия -это первая причина для выбора синтетических простагландинов в качестве препаратов первого выбора в лечении глаукомы [6,7,19,21].…”
Section: клінічна офтальмологія введениеunclassified
“…The higher the IOP, the greater the risk of optic nerve damage, visual loss, and blindness. [ 1 2 3 ] Early, pressure-lowering treatment is a dominant cost-effective treatment strategy over a strategy to start the same treatment approach later, after glaucoma has occurred for patients with ocular hypertension. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to the Early Manifest Glaucoma Trial (EMGT), every 1 mm Hg of IOP lowering further reduced the risk of glaucomatous progression 3. Topical prostaglandin analogues (PGAs) have become the mainstay of initial medical treatment due to their efficacy and safety in lowering IOP 4. Generic latanoprost is the most commonly prescribed PGA although clinical trials reported a greater reduction in IOP in patients with open-angle glaucoma (OAG) or ocular hypertension (OHT) with bimatoprost 0.03% compared with either travoprost 0.004% or latanoprost 0.005% in some instances 5.…”
mentioning
confidence: 99%